Fun Math Learning For Elementary School Students Through Interactive Puzzle Media - Ramlah Ramlah; Nancy Riana; Agung Prasetyo Abadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
Amid the covid-19 pandemic, teachers and students should undergo an educational transformation which suddenly force them to embrace digital learning to support an online mode of teaching. In mathematic context, teachers can make use of interactive puzzle media as one of the digital tools that may stimulate activeness, mathematical understanding, and fun math learning for students. The purpose of this study is therefore to unearth the students’ reception during mathematics instruction using the media. This descriptive qualitative research involved 30 first graders of elementary school in West Java, Indonesia and employed questionnaire, interview, and video-based observation to collect the data. The research findings showcase that learning mathematics using interactive puzzle media is enjoyable for students, and there is a strongly positive response from 80% of them which can be seen from the activeness and enthusiasm demonstrated during the learning process. It further indicates that the application of interactive puzzle media increases students' confidence, fosters learning motivation, develops self-reliant learning, and provides clearer understanding of recognizing the concept of numbers and recognize the concept of numbers and geometric shapes. With these specialties, interactive puzzle would be appropriate instructional media and technology for learning. Interactive puzzle media can be accessed online through http://bit.ly/MediaPuzzleInteraktif